Adaptive ground segmentation method for real-time mobile robot control. (21st December 2017) - Vu, Hoang; Nguyen, Hieu Trong; Chu, Phuong Minh; Zhang, Weiqiang; Cho, Seoungjae; Park, Yong Woon; Cho, Kyungeun
For an autonomous mobile robot operating in an unknown environment, distinguishing obstacles from the traversable ground region is an essential step in determining whether the robot can traverse the area. Ground segmentation thus plays a critical role in autonomous mobile robot navigation in challenging environments, especially in real time. In this article, a ground segmentation method is proposed that combines three techniques: gradient threshold, adaptive break point detection, and mean height evaluation. Based on three-dimensional (3D) point clouds obtained from a Velodyne HDL-32E sensor, and by exploiting the structure of a two-dimensional reference image, the 3D data are represented as a graph data structures. This process serves as both a preprocessing step and a visualization of very large data sets, mobile-generated data for segmentation, and building maps of the area. Various types of 3D data—such as ground regions near the sensor center, uneven regions, and sparse regions—need to be represented and segmented. For the ground regions, we apply the gradient threshold technique for segmentation. We address the uneven regions using adaptive break points. Finally, for the sparse region, we segment the ground by using a mean height evaluation.